p97 Inhibitors Possessing Antiviral Activity Against SARS-CoV-2 and Low Cytotoxicity - Rui Ding; Tiffany C. Edwards; Prithwish Goswami; Daniel J. Wilson; Christine D. Dreis; Yihong Ye; Robert J. Geraghty; Liqiang Chen (Pharmaceuticals)
Background: p97 (also known as valosin-containing protein, VCP) is a member of the AAA+ ATPase family and is intimately associated with protein quality control and homeostasis regulation. Therefore, pharmaceutical inhibition of p97 has been actively pursued as an anticancer strategy. Recently, p97 has emerged as an important pro-viral host factor and p97 inhibitors are being evaluated as potential antiviral agents. Methods: We designed and synthesized novel p97 inhibitors based on the rearrangement of the central fused ring of our previously reported p97 inhibitors. These compounds were tested for inhibition of p97, cytotoxicity, and antiviral activity against SARS-CoV-2. Molecular docking was also performed on selected inhibitors to shed light on their binding modes. Results: Among these new p97 inhibitors, two compounds possess enhanced anti-p97 activity over their parent compounds. More significantly, these two inhibitors exhibit strong antiviral activity against SARS-CoV-2 at doses with no significant cytotoxicity. Molecular docking reveals no major change of the binding mode relative to that of their parent compounds, further supporting our design strategy. Conclusions: These compounds are structurally novel p97 inhibitors that display low toxicity and possess promising antiviral activity against SARS-CoV-2 and potentially other viruses. Further structural exploration is therefore justified and improved analogs will serve as useful tools for studying p97 as a promising host antiviral target.